Interacción entre factores ambientales y raciales sobre la prevalencia de hemotrópicos en hembras bovinas doble propósito en sabanas inundables araucanas, Colombia (2018)
The objective of this work was to determine the prevalence of hemotropics A. marginale, Babesia spp. and Trypanosoma spp. and environmental and genetic interactions in milking cows of the dual purpose system in the Municipality of Arauca, Colombia. A blood sample from the middle coccygeal vein was collected from 333 female bovines of different ages, located on 18 livestock farms, and the inclusion criterion was only the females that were milked at each farm. Sampling was performed for convenience in summer and winter. Samples were analyzed using Wright and Hemacolor® techniques. The racial groups were: Cebu (n = 157), Criolla (n = 14), Criolla x Cebu (n = 32), Mestiza (n = 64), Brown x Cebu (n=22), Simental x Cebu (n = 16) and Holstein x Cebu (n = 5). Through contingency tables the percentage amount of animals positive to hemotrópics was determined. The data were processed in Infostat; 72.22% of farms were positive for A. marginale; 66.66% for Trypanosoma spp and 16.66% for Babesia spp. The overall prevalence was 43.54%, the most frequent hemoparasite was A. marginale, (24.92%), followed by Trypanosoma spp, (14.41%) and Babesia spp (4.2%). No mixed infections were identified. A significant association (P = 0.0001) of the farms with the three hemoparasites was observed; A. marginale was dependent on the racial group (P = 0.0046), Babesia spp and A. marginale had time-of-year dependence (P < 0.05), Anaplasma marginale was related to females of more than five births (P = 0.0410) and the number of deliveries showed no interaction (P > 0.05). It is concluded that in the Araucanian floodplain region the highest prevalence of hemoparasites was associated with A. marginale and Trypanosoma spp, Animals with a predominance of taurus are more susceptible than Creoles and the interactions are given to general management, sanitary program, time and agroecological location of livestock farms. © Universidad del Zulia 2018, Derechos Reservados. Maracaibo, Venezuela. Acerca de LUZ Web. Ayuda.